2018
DOI: 10.1093/ntr/nty005
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Analysis and Simulated Pyrolysis of Tobacco Heating System 2.2 Compared to Conventional Cigarettes

Abstract: To our knowledge, few independent studies of HNB products have been published. In this paper, a comprehensive list of chemical releases was tested systematically and compared to those from 3R4F. Although THS 2.2 generates lower levels of harmful constituents, the nicotine and tar levels were almost identical to 3R4F.The results should be discussed carefully in the future when assess the dual-use with other conventional cigarettes, nicotine dependence of HNB products, etc. This study also suggests that regulato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
92
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 114 publications
(102 citation statements)
references
References 35 publications
6
92
0
4
Order By: Relevance
“…selected indoor air constituents were measured -the concentrations of respirable suspended particles, ultraviolet particulate matter, fluorescent particulate matter, solanesol, 3-ethenylpyridine, formaldehyde, acrolein, crotonaldehyde, acrylonitrile, benzene, 1,3-butadiene, isoprene, toluene, CO, NO and NO x after the use of THS2.2 under 3 environmental conditions were equivalent to the concentrations found in background indoor air -THS2.2 use resulted in increased acetaldehyde and nicotine concentrations in indoor air, but these concentrations were considerably lower than those found in conventional cigarettes The tobacco industry claims that the aerosol formed during the heating process has around 90-95% lower levels of toxicants than conventional cigarette smoke [13][14][15]23,24]. This was partially confirmed by independent studies [27,28]. Li et al reported that, compared to conventional cigarettes, IQOS delivered a > 90% lower concentration of harmful and potentially harmful constituents (HPHCs) except for carbonyls, ammonia, and N-nitrosoanabasine, where the levels were about 50-80% lower [27].…”
Section: Chemical Composition Of Tobacco Sticksmentioning
confidence: 66%
See 3 more Smart Citations
“…selected indoor air constituents were measured -the concentrations of respirable suspended particles, ultraviolet particulate matter, fluorescent particulate matter, solanesol, 3-ethenylpyridine, formaldehyde, acrolein, crotonaldehyde, acrylonitrile, benzene, 1,3-butadiene, isoprene, toluene, CO, NO and NO x after the use of THS2.2 under 3 environmental conditions were equivalent to the concentrations found in background indoor air -THS2.2 use resulted in increased acetaldehyde and nicotine concentrations in indoor air, but these concentrations were considerably lower than those found in conventional cigarettes The tobacco industry claims that the aerosol formed during the heating process has around 90-95% lower levels of toxicants than conventional cigarette smoke [13][14][15]23,24]. This was partially confirmed by independent studies [27,28]. Li et al reported that, compared to conventional cigarettes, IQOS delivered a > 90% lower concentration of harmful and potentially harmful constituents (HPHCs) except for carbonyls, ammonia, and N-nitrosoanabasine, where the levels were about 50-80% lower [27].…”
Section: Chemical Composition Of Tobacco Sticksmentioning
confidence: 66%
“…This was partially confirmed by independent studies [27,28]. Li et al reported that, compared to conventional cigarettes, IQOS delivered a > 90% lower concentration of harmful and potentially harmful constituents (HPHCs) except for carbonyls, ammonia, and N-nitrosoanabasine, where the levels were about 50-80% lower [27]. Farsalinos et al showed that IQOS use emitted substantially lower levels of carbonyls than a commercial cigarette but higher levels than an e-cigarette [28].…”
Section: Chemical Composition Of Tobacco Sticksmentioning
confidence: 84%
See 2 more Smart Citations
“…W odniesieniu do e-papierosów typu heat-not-burn (podgrzewacze tytoniu) zaobserwowano znacznie niższą zawartość substancji toksycznych i kancerogennych wytwarzanych podczas ich użytkowania, w porównaniu z papierosami tradycyjnymi. Stwierdzono natomiast porównywalną zawartość substancji smolistych oraz nikotyny [30]. Uzyskane dane wskazują, że użycie urządzenia typu IQOS zmniejsza emisję niektórych szkodliwych związków, ale jednocześnie zwiększa ekspozycję na inne substancje, o nieznanej toksyczności [31].…”
Section: E-palenie a Zdrowieunclassified